1127. Validation of an Adult and Pediatric Beta-Lactam Allergy Risk Stratification Tool. (4th December 2021) - Jaffa, Rupal K; Ton, Minh-Thi; Forrester, Jeanne; Patel, Rupal; Brantley, Courtney W; Campbell, Jamie; Carlson, Travis J; Morris, Lee; Patel, Niraj C; Shah, Ekta; Boger, Michael S; Davidson, Lisa
Abstract: Background: Penicillin allergies are commonly reported, yet more than 95% of these patients can tolerate β-lactams. A comprehensive allergy history is essential when determining which patients can safely receive a β-lactam but is rarely obtained. When available, interpretation of the history is often limited by lack of comfort in determining risk of an allergic reaction. Our antimicrobial stewardship and allergy team created a standardized allergy history questionnaire and risk stratification tool. The purpose of this study was to validate this tool by comparing risk levels assigned by various clinicians to that assigned by an allergist. Methods: We prospectively identified 50 adult and 50 pediatric patients hospitalized between July 1, 2020 and March 31, 2021 with an allergy to penicillin, amoxicillin, ampicillin, or cephalexin. Patients with severe non-IgE mediated reactions were excluded. All patients (or caregivers) were interviewed by the same pharmacist using the allergy questionnaire. Clinicians from various subspecialties, including an adult and pediatric allergist, an adult and pediatric infectious diseases (ID) physician, an adult and pediatric hospitalist, and an adult and pediatric ID pharmacist, received anonymized completed questionnaires and the risk stratification tool, but were blinded to other clinicians' responses. The primary endpoint was overall concordance in risk stratification between non-allergists and allergists. Results: Overall concordance was 66% (33/50) in adult and 90% (45/50) in pediatric patients (Table 1). Concordance between individual clinicians and the allergist are shown in Figure 1. In adults, anaphylaxis, difficulty breathing, and angioedema were associated with less severe stratification by non-allergists than allergists. No clinicians stratified any pediatric patient into a lower risk category than the allergist. Table 1. Clinician Agreement with Allergist Figure 1. Risk Stratification Severity Compared to Allergist Conclusion: Use of a β-lactam allergy risk stratification tool led to agreement with allergist assessment in the majority of patients. Variation in risk assignment was greater in adult patients; however, non-allergist pediatric providers assigned all patients at the same or more severe level as the allergist, indicating safety in this population. Disclosures: All Authors : No reported disclosures